An overview of the cross-cultural business negotiation between Malaysia and Australia. - Ismail, Jumiati; Azariadis, Michael; Jusoff, Kamaruzaman (Canadian Academy of Oriental and Occidental Culture, 2009)
This paper aims to explore communication deviances and strategies in the negotiation discourse of Malaysian-Australian business encounters, from both a linguistic and non-linguistic perspective. Specifically, it sees miscommunications/deviances as factors that may hinder the business communication process and prevent the negotiators from achieving their objectives. The study also focuses on strategies, or those discourse skills which promote successful business Malaysia-Australia negotiation.